Communication culture of regional PDAM Sleman during the Covid-19 pandemic - Ratna Pradipta, Meylasari; Akbar Sugiantoro, Hari (COMMICAST, 2022)
The presence of Corona Virus Desease (Covid-19) as a new variant virus brings many changes in the system and policies of a country. Various prevention efforts are carried out by the government. The Covid-19 pandemic had a significant influence on an organization's communication culture in a company. With theCovid-19 pandemic making the communication culture of organizations in a company change drastically, Anggota organization must learn the communication culture with new adaptations. This study uses descriptive qualitative research methods, Metode is related between researchers and informants directly. The purpose of this study is to find out how the communication of PDAM Sleman organization in the pandemic period is dissected using 4 organizational communication functions. And the result of this study is that PDAM Sleman has been effective in using 4 organizational communication functions even in pandemic times like now.